Civil society brief Mongolia. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It provides information on the country major CSOs, the legal and regulatory frameworks they operate under, and the current state of government CSO cooperation. Recommendations focus on how some of the capacity constraints facing CSOs such as financial sustainability can be addressed.
Keywords: Public administration; Asian Development Bank; Electronic book